The Relationship between paleotemperatures, burial depth and diagenesis in the Lower Cretaceous sandstones of the Peace River, Spirit River and Gething Formations of northwest Alberta ... - Stromquist, Barbara Haworth Adams, 1958- (University of Calgary, 1985)
Bibliography: p. 125-128. ...